ANALISIS RASIO LIKUIDITAS DAN RASIO PROFITABILITAS TERHADAP PERUBAHAN LABA - Andayani, Mery; Ardini, Lilis (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to find out the influence of liquidity ratio and profitability ratio to the changes in profit at Property and Real Estate companies which are listed in Indonesia Stock Exchange (IDX). In this research the liquidity ratio of the company is measured by using Current ratio and Quick ratio whereas profitability ratio is measured by using Return on Asset and Return on Equity. The research sample has been obtained by using purposive sampling method. The data analysis which has been carried out in order to test the hypothesis has been done by using the multiple linear regression analysis.Based on the result of the research of model feasibility test (Goodness of Fit) states that these variables i.e.: current ratio, quick ratio, return on asset, and return on equity are feasible to be used to explain changes in profit variable. The result of t test partially shows that current ratio and quick ratio has insignificant to the changes in profit whereas return on asset and return on equity has significant to the changes in profit.Keywords: Current ratio, quick ratio, return on asset, return on equity, changes in profit